Implementation of Extracurricular Activities in Developing Students' Interests and Talents - Martadiningsih, Dhora Ayu; Nirina, Andriamiandrisoa Mamy (Nur Science Institute, 2024)
Background: This study aims to (1) Explain the extracurricular implementation that has been applied at SD Muhammadiyah PK Kottabarat Surakarta in developing students' talent interests, (2) Describe school perceptions about the importance ofdeveloping students' talent interests, (3) Describe the steps or efforts taken by the school in developing the interests of student talent at SD Muhammadiyah PK Kottabarat Surakarta, (4) Explain the obstacles experienced by PK Muhammadiyah Elementary School Kottabarat Surakarta in developing students' interest in talent. Method: This research is a qualitative research. Data collection uses interviews, observation and documentation. The validity of the data uses source triangulation and method / technique triangulation. Result: The results obtained are the development of interest in talent by discovering the potential of children, channeling each of their talents into extracurricular activities that are honed and trained so that it becomes an achievement. The school's perception of developing students' talent interests is very important. Student talent interests must be explored and developed according to each child's expertise. Steps taken by the school by way of scrining new students. Then directed to follow the three compulsory extra curricular namely swimming, painting and dance. Students are required to choose an extracurricular out of 13 existing extra curricular. The extracurricular selection is done by filling out a questionnaire given to students and parents. The constraints faced when developing talent interests are the parent factor and the friend factor.